ROLE OF THIRD-PARTY LOGISTICS SERVICES ON SUPPLY CHAIN PERFORMANCE IN DISTRIBUTION SECTOR IN KENYA: A CASE OF BOLLORE TRANSPORT & LOGISTICS KENYA LIMITED - Maata, Samson Wandera; Ombui, Dr. Kepha (International Journal of Supply Chain Management, 2018)
Purpose: The main objective of the study was to determine the role of third-party logistics services on supply chain performance in distribution sector in Kenya. Methodology: The study adopted a descriptive research design. The target population of the study was all employees working within Bollore Transport & Logistics Kenya Limited Nairobi office. The study sampled 41 respondents out of 138 staff who work in the Logistics and transport department and 40 respondents participated in the final study. The researcher adopted the simple random sampling method because it gives every member of the population equal chances of being selected. A questionnaire was developed and pre-tested as the main tool for collecting primary data and was delivered to the respondents directly with the help of research assistants and picked later at the agreed date. The questionnaire contained both open and close ended questions. Data analysis was analysed by use of statistical package for social science version 24 (SPSS) analysis software and t-Trend analysis. The findings were presented using descriptive statistical tools like graphs, tables and other measures of central tendency while qualitative data was analyzed to establish patterns, trends and relationships from the information gathered. Results: The results of the study revealed that the four variables studied explain 83% of variance and that other factors not included in this research contribute 17% of variance in the dependent variable. The study also established that ICT integration leads in improving financial performance in supply chain performance within distribution sector in Kenya while organizational policy adds little value on financial performance of firms within supply chain. Unique Contribution to Theory, Practice and Policy: The study recommends that the Government should implement distribution legislation to remove the unwanted and unfair clearance procedures that firms undergo delays 3PLs to achieve their targeted lead -times to customers. The Third Party Logistics Services (3PLs) providers need to build a culture of information sharing among its personnel, and with external clients hence reduce logistics obstacles of lack of knowledge within the supply chain sector.